Long term overheating failure of a closed recirculation system water cooling pipe - Mohd Arif Anuar, Mohd Salleh; Shaiful Rizam, Shamsudin; Azmi, Kamardin; Hafizan, Hassan (SIRIM, 2011)
4th Malaysian Powder Metallurgy Symposium (MPMS) and Malaysian Metallurgical Conference (MMC) 2010 organized by SIRIM Berhad on 22nd - 23rd November 2010 at Parkroyal Hotel, Penang, Malaysia.